Zaměstnanecké benefity - Matuška, František (Vysoké učení technické v Brně. Fakulta podnikatelská, 2014)
Tato bakalářská práce se zabývá deskripcí zaměstnaneckých benefitů, způsobem jejich používání ze strany zaměstnavatelů a čerpání ze strany zaměstnanců a v neposlední řadě charakterizuje důvody jejich používání. Práce řeší daňové a účetní aspekty zaměstnaneckých výhod a u vybraných druhů benefitů stanovuje jejich řešení z pohledu české legislativy.

The aim of this bachelor thesis is to describe benefits of employees and the manner in which they are used by employers and utilized by employees; it also concerns arguments for their utilization. The thesis examines tax and accounting aspects of the benefits of employees and determines a solution to the selected types of the benefits from the perspective of Czech legislation.
Employee’s Benefits
Keywords: Zaměstnanecké výhody; benefity; účetnictví; daně; zaměstnavatel; Employee’s benefits; benefits; accounting; taxes; employer